Exploratory Analysis of Risk Management Process of UAE Police Department - Omair Juma, Abdulla Ahmed Zaher; A. Perumal, Puvanasvaran; Mansoor, Nusaibah (International Journal of Sustainable Construction Engineering and Technology, 2022)
Risk control and management are becoming increasingly important in many organisational operations. It goes beyond the business sector to include security organisations like police departments. The fact that police officers engage in a wide range of daily activities that expose them to a variety of potentially hazardous situations Police risk management includes both physical and financial aspects. Risk identification is the first step in the risk management process, followed by risk analysis, risk evaluation, and risk treatment. According to the literature, the Dubai Police Department has no framework in place to fully manage risks and evaluate the effectiveness of police operations. Early warning systems are critical for detecting potential severe RM because police departments must rely on them to manage risks and keep track of any potential new risks. As a result, the UAE police department’s risk management strategy was investigated in this paper. It classified the data collection process using exploratory factor analysis, which was a quantitative approach. A self-administered survey yielded 381 valid questionnaires from Dubai Police Department officers. The study’s findings revealed that risk identification, risk analysis, risk evaluation, and risk response are the four fundamental steps of effective risk management. The Crobach Alpha test was used to assess the consistency and reliability of the data, and the result was 0.814, indicating that the data is suitable for use. Only one of the twenty indicators, which were divided into four groups for risk management, was weak according to outliers and communalities tests. The risk management process was accurately described by another 20 factors. Total variance extraction yielded a rate of 57.130 percent, which was higher than the required 50%. As a result, the risk management procedure investigated in this study may be useful for effectively managing risks in the UAE police force.